Prediksi Masa Layan Beton Bertulang pada Lingkungan Klorida Menggunakan Model Laju Korosi - Alfa Reza (Jurnal Teknik Sipil Terapan (JTST), 2026)
Reinforcement corrosion is one of the primary causes of performance deterioration in reinforced concrete structures exposed to chloride-containing environments. This study aims to analyze the corrosion resistance of metakaolin-based geopolymer mortar and to predict the service life of reinforced concrete structures through the integration of laboratory testing results and analytical approaches. The method employed was an accelerated corrosion experiment using a 5% NaCl solution and a 12 V DC power supply under wet–dry cyclic conditions. The parameters analyzed included corrosion rate, corrosion current density, and percentage of steel weight loss. The results indicate that geopolymer mortar with the MK-95 composition exhibited the best performance, showing lower corrosion rate and corrosion current density compared to normal mortar (MN) and MK-100. Service life prediction was conducted by integrating the corrosion rate model with a chloride diffusion approach based on Tuutti’s concept. The results show that the estimated service life is 38 years for MN, 30 years for MK-100, and up to 153 years for MK-95. Furthermore, the analysis of concrete cover thickness demonstrates that the use of geopolymer mortar enables the achievement of longer service life with more efficient cover thickness that still falls within standard design requirements. Therefore, the use of metakaolin-based geopolymer mortar, particularly at the optimum composition, is proven to be effective in enhancing the durability of reinforced concrete structures in corrosive environments. Keywords—reinforced concrete, corrosion, metakaolin, geopolymer mortar, service life